‘She's sort of breathing’: What linguistic factors determine call-taker recognition of agonal breathing in emergency calls for cardiac arrest? - Riou, Marine; Ball, Stephen; Williams, Teresa; Whiteside, A.; Cameron, P.; Fatovich, D.; Perkins, G.; Smith, K.; Bray, J.; Inoue, Madoka; O'Halloran, Kay; Bailey, P.; et al. (Elsevier, 2018)
Background: In emergency ambulance calls, agonal breathing remains a barrier to the recognition of out-of-hospital cardiac arrest (OHCA), initiation of cardiopulmonary resuscitation, and rapid dispatch. We aimed to explore whether the language used by callers to describe breathing had an impact on call-taker recognition of agonal breathing and hence cardiac arrest. Methods: We analysed 176 calls of paramedic-confirmed OHCA, stratified by recognition of OHCA (89 cases recognised, 87 cases not recognised). We investigated the linguistic features of callers’ response to the question “is s/he breathing?” and examined the impact on subsequent coding by call-takers. Results: Among all cases (recognised and non-recognised), 64% (113/176) of callers said that the patients were breathing (yes-answers). We identified two categories of yes-answers: 56% (63/113) were plain answers, confirming that the patient was breathing (“he's breathing”); and 44% (50/113) were qualified answers, containing additional information (“yes but gasping”). Qualified yes-answers were suggestive of agonal breathing. Yet these answers were often not pursued and most (32/50) of these calls were not recognised as OHCA at dispatch. Conclusion: There is potential for improved recognition of agonal breathing if call-takers are trained to be alert to any qualification following a confirmation that the patient is breathing.